Attosecond Rabi oscillations in high harmonic generation resonantly driven by extreme ultraviolet laser fields - Alba de las Heras; Carlos Hernández-García; Javier Serrano; Aleksandar Prodanov; Dimitar Popmintchev; Tenio Popmintchev; Luis Plaja (Physical Review Research)
High-order harmonic generation driven by intense extreme ultraviolet (EUV) fields merges quantum optics and attosecond science, giving rise to an appealing route for the generation of coherent EUV and soft x-ray light for high-resolution imaging and spectroscopies. We theoretically investigate ultrafast resonant dynamics during the interaction of He atoms with strong extreme ultraviolet pulses. At high driving intensities, we identify record fast attosecond Rabi oscillations imprinting observable signatures in the high harmonic spectrum. At field strengths suppressing the Coulomb potential barrier for all the bound states, we demonstrate the survival of the attosecond two-level dynamics for several Rabi cycles. Consequently, this intense EUV laser-atom interaction reveals a strong-field scenario in which resonant coupling of two-level bound-bound transitions prevails, in contrast to the bound-continuum transitions typically dominant in conventional infrared strong-field regimes. Our findings of a high-frequency up-conversion regime combining two coexisting pathways—a two-level coupling and a bound-continuum coupling—set an interesting perspective for extreme attosecond nonlinear optics with intense short-wavelength laser fields.